Relationship between Arm Span and Body Height in Preschool Children of the Urhobo Ethnic Group in Abraka, Delta State, Nigeria - Oghenesuvwe, Enakpoya Princess; Taniyohwo, Enaohwo Mamerhi; Marymagdalene, Ebijor Elohor; Oluwakemi, Kaine Omashim; Chidima, Onyeka Victory; Godswill, Okoro Ogheneyebrorue; Eboh, D E O (International Journal of Human and Health Sciences (IJHHS), 2025)
Background: Among various anthropometric measures, arm span and height stand out as primary indicators of growth and physical development in children. Objective: To determine the correlation between the height and arm span in preschool children of the Urhobo ethnic group in Abraka in Delta State, Nigeria. It also aims to establish a formula for estimation of height using the arm span in this population. Methods: This descriptive cross-sectional study was carried out among two hundred children (99 male and 101 female) aged 3 and 5 years belonging to the Urhobo ethnic group, who were randomly selected from nursery schools. Standard anthropometric techniques were used to measure height and arm span. Pearson’s coefficients of correlation and regression equations were calculated. Results: The mean and standard deviation of the height of males and females were 107.43±8.98cm and 105.59±8.83cm respectively and that of arm span of males and females were 108.58±9.95cm and 106.39±9.44cm respectively. The differences were not statistically significant (p>0.05). However, a positive correlation was observed between the height and the arm span parameters (R²=0.936). A regression formula of height was provided (H=14.22+0.86 AS), as per our data analysis. Conclusion: In Conclusion arm span was found to be a valid measure of the height. Hence, arm span can be used as a reliable predictor of height in children with disabilities. These findings could be of practical significance in monitoring growth and development in children. International Journal of Human and Health Sciences Vol. 09 No. 03 Jul’25 Page: 165-170